Management of acute ischemic stroke in patients with COVID-19 infection: Insights from an international panel - Qureshi, Adnan I.; Abd-Allah, Foad; Al-Senani, Fahmi; Aytac, Emrah; Borhani-Haghighi, Afshin; Ciccone, Alfonso; Wang, Yongjun (W B Saunders Co-Elsevier Inc, 2020)
Objective: To present guidance for clinicians caring for adult patients with acuteischemic stroke with confirmed or suspected COVID-19 infection. Methods: The summary was prepared after review of systematic literature reviews,reference to previously published stroke guidelines, personal files, and expert opinion by members from 18 countries. Results: The document includes practice implications for evaluation of stroke patients with caution for stroke team members to avoid COVID-19 exposure, during clinical evaluation and conduction of imaging and laboratory procedures with special considerations of intravenous thrombolysis and mechanical thrombectomy in stroke patients with suspected or confirmed COVID-19 infection. Results: Conclusions-The summary is expected to guide clinicians caring for adult patients with acute ischemic stroke who are suspected of, or confirmed, with COVID-19 infection. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Corona virus; Acute stroke; Mechanical thrombectomy; Thrombolysis; Ischemic stroke; COVID-19